Effects of microwave on drug release responses of spray-dried alginate microspheres / Ekha Mardziah Radman - Radman, Ekha Mardziah (2010)
The behavior of rigid guluronic acid-rich (MG) and flexible mannuronic acid-rich (MC) alginate in controlling drug release responses of spray-dried microspheres against microwave was investigated using sodium diclofenac as model water-soluble drug. MC microspheres required a shorter period of microwave irradiation to reduce drug release extent than MG microspheres. In response to microwave, the drug release profiles of 1:1 MG-MG microspheres resembled MC microspheres. The state of polymer-polymer and drug-polymer interaction via 0-H and/or N-H moiety of microspheres was affected by alginate chain flexibility under the influence of microwave. It then governed the drug release responses of microspheres.